Eu vivo à beira - Gonçalves, Marcia Luisa Bastilho (2020)
The present work, divided into two parts, contains in its content the novel Eu vivo à beira, narrated by Luisa, a writer in crisis for not being able to write because she believes she is not able to do it alone, now that the characters she saw during her life have disappeared, those who shared her same reality, always hovering around her, and who inspired her stories. The novel features, in addition to Luisa's story, the first nine fantasy story chapters that were written and published by Luisa. In the second part of this work, A desconstrução de Luisa, we have a reflective essay on the creation of the novel, the journey taken during its writing, permeated by theoretical elements.